PENGEMBANGAN INSTRUMEN PENALARAN MATEMATIS UNTUK MENSTIMULASI KEMAMPUAN NUMERASI SISWA DENGAN KONTEKS “RUMAHKU” - Suriyani .; Mona Sri Wahyuni (Institut Pendidikan Tapanuli Selatan, 2021)
The objectives of this study are: 1) To produce valid and effective mathematical reasoning instruments. 2) To determine students' numeracy abilities after being given mathematical reasoning instruments in the context of